2023
DOI: 10.3389/fphar.2023.1241578
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl-induced reward seeking is sex and dose dependent and is prevented by D-cysteine ethylester

Zackery T. Knauss,
Caden J. Hearn,
Nathan C. Hendryx
et al.

Abstract: Introduction: Despite their inclination to induce tolerance, addictive states, and respiratory depression, synthetic opioids are among the most effective clinically administered drugs to treat severe acute/chronic pain and induce surgical anesthesia. Current medical interventions for opioid-induced respiratory depression (OIRD), wooden chest syndrome, and opioid use disorder (OUD) show limited efficacy and are marked by low success in the face of highly potent synthetic opioids such as fentanyl. D-Cysteine eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Many questions remain regarding the potential use of L-thiol esters as therapeutics for key clinical problems associated with opioid analgesia in humans, including: 1) if L-CYSee attenuates/blocks self-administration of opioids in OUD patients, adding it to prescription opioids may result in lower drug abuse or addiction potential; 2) if L-CYSee attenuates or blocks development of physical dependence on opioids, then adding it to prescription opioids will minimize and may potentially eliminate physical dependence in individuals who receive opioids for a long-term basis, such as everyday, all day, for weeks/months; 3) if L-CYSee attenuates/blocks tachyphylaxis to opioid analgesia or hyperalgesia caused by opioids, then the addition of L-CYSee to prescription opioids will maintain their analgesic efficacy over long periods of time, eliminating the development of tolerance, need for escalating doses, and potential complications of hyperalgesia; 4) if L-CYSee has several of the advantageous effects observed in rodents, then adding it to opioid analgesics would multiply the beneficial aspects of the opioids; 5) if L-CYSee prevents the development of physical dependence, and specifically, if it is introduced to an individual with physical dependence and attenuates/blocks opioid withdrawal, it could be used as an outpatient/inpatient medication to manage opioid withdrawal in those who are iatrogenically physically dependent (long-term opioid prescriptions) or those who are addicted and physically dependent; 6) if L-CYSee attenuates/blocks euphoria and/or the development of physiological dependence to opioids, then it would be a good medication for medication-assisted treatment (MAT) and a potentially good drug for harm reduction interventions in people with OUD who are not interested in the psychosocial aspects of counseling and treatment; 7) as some patients with a history of OUD who are currently sober need opioids for the treatment of acute or chronic pain syndromes, this L-thiol ester, if it attenuates or blocks euphoria and physical dependence, could be added to opioid analgesics when given to people with a history of OUD, thereby eliminating the risk of opioid analgesic-precipitating euphoria, drug cravings, and their markedly increased risk of relapse; 8) if L-CYSee attenuates/blocks euphoria from chemically mediated dopamine surges within the ventral tegmentum, nucleus accumbens, or medial prefrontal cortex, where brain rewarding euphoria-producing dopamine surge happens from all drugs of abuse/addiction ( Deslandes et al, 2002 ; Gardner, 2011 ; Koob and Volkow, 2016 ; Volkow et al, 2019 ; Koob, 2020 ; Sakloth et al, 2020 ), then it will be useful in the treatment of OUD and other SUDs; and 9) if L-CYSee attenuates/blocks euphoria from chemically mediated dopamine surges, it could be combined with or added to all controlled prescription drugs, resulting in an abuse-resistant or non-abusable form of prescribed opioids, benzodiazepines, and psychostimulants. In relation to point (1), we recently showed that co-administration of the D-isomer, D-cysteine ethyl ester, with fentanyl prevents the development of fentanyl-induced conditioned place preference in both male and female rats ( Knauss et al, 2023 ). Thus, L,D-thiol esters likely reduce the rewarding properties of opioids and reduce their addictive potential.…”
Section: Discussionmentioning
confidence: 99%
“…Many questions remain regarding the potential use of L-thiol esters as therapeutics for key clinical problems associated with opioid analgesia in humans, including: 1) if L-CYSee attenuates/blocks self-administration of opioids in OUD patients, adding it to prescription opioids may result in lower drug abuse or addiction potential; 2) if L-CYSee attenuates or blocks development of physical dependence on opioids, then adding it to prescription opioids will minimize and may potentially eliminate physical dependence in individuals who receive opioids for a long-term basis, such as everyday, all day, for weeks/months; 3) if L-CYSee attenuates/blocks tachyphylaxis to opioid analgesia or hyperalgesia caused by opioids, then the addition of L-CYSee to prescription opioids will maintain their analgesic efficacy over long periods of time, eliminating the development of tolerance, need for escalating doses, and potential complications of hyperalgesia; 4) if L-CYSee has several of the advantageous effects observed in rodents, then adding it to opioid analgesics would multiply the beneficial aspects of the opioids; 5) if L-CYSee prevents the development of physical dependence, and specifically, if it is introduced to an individual with physical dependence and attenuates/blocks opioid withdrawal, it could be used as an outpatient/inpatient medication to manage opioid withdrawal in those who are iatrogenically physically dependent (long-term opioid prescriptions) or those who are addicted and physically dependent; 6) if L-CYSee attenuates/blocks euphoria and/or the development of physiological dependence to opioids, then it would be a good medication for medication-assisted treatment (MAT) and a potentially good drug for harm reduction interventions in people with OUD who are not interested in the psychosocial aspects of counseling and treatment; 7) as some patients with a history of OUD who are currently sober need opioids for the treatment of acute or chronic pain syndromes, this L-thiol ester, if it attenuates or blocks euphoria and physical dependence, could be added to opioid analgesics when given to people with a history of OUD, thereby eliminating the risk of opioid analgesic-precipitating euphoria, drug cravings, and their markedly increased risk of relapse; 8) if L-CYSee attenuates/blocks euphoria from chemically mediated dopamine surges within the ventral tegmentum, nucleus accumbens, or medial prefrontal cortex, where brain rewarding euphoria-producing dopamine surge happens from all drugs of abuse/addiction ( Deslandes et al, 2002 ; Gardner, 2011 ; Koob and Volkow, 2016 ; Volkow et al, 2019 ; Koob, 2020 ; Sakloth et al, 2020 ), then it will be useful in the treatment of OUD and other SUDs; and 9) if L-CYSee attenuates/blocks euphoria from chemically mediated dopamine surges, it could be combined with or added to all controlled prescription drugs, resulting in an abuse-resistant or non-abusable form of prescribed opioids, benzodiazepines, and psychostimulants. In relation to point (1), we recently showed that co-administration of the D-isomer, D-cysteine ethyl ester, with fentanyl prevents the development of fentanyl-induced conditioned place preference in both male and female rats ( Knauss et al, 2023 ). Thus, L,D-thiol esters likely reduce the rewarding properties of opioids and reduce their addictive potential.…”
Section: Discussionmentioning
confidence: 99%